Tensor-based MIMO relaying communication systems - Ximenes, Leandro Ronchini (2015)
In cooperative communication systems, two or more transmitting terminals are combined to increase the diversity and/or the power of the signals arriving at a particular receiver. Therefore, even if the devices do not have more than one antenna, or if a significant propaga- tion loss is present between the two communicating nodes, the various transmitting elements can act as a virtual antenna array, thus obtaining the benefits of the multiple antenna (MIMO) systems, especially the increase in the capacity. Recently, tensor decompositions have been introduced as an efficient approach for channel estimation in cooperative com- munication systems. However, among the few works devoted to this task, the utilization of the PARAFAC tensor decomposition for modeling the received signals did not allow the development of techniques for joint symbol and channel estimation. Aiming to avoid the use of pilot sequences, which limits the overall spectral efficiency by dedicating a portion of the bandwidth only for the channel estimation task, the objective of this thesis is to provide new tensor-based strategies, including transmission systems and semi-blind receivers, for one-way two-hop MIMO relaying systems. Based on a Khatri-Rao space-time coding at the source and two different Amplify-and-Forward (AF) relaying strategies, two transmission schemes are proposed. For these systems, named PT2-AF and NP-AF, the received signals at the destination node follow respectively a PARATUCK2 and a nested PARAFAC tensor model. Exploiting uniqueness properties of these tensor models which are established in the thesis, several semi-blind receivers are derived. Some of these receivers are of iterative form us- ing an ALS algorithm, whereas some other ones have closed-form solutions associated with Khatri-Rao factorizations. Some simulation results are finally presented to illustrate the per- formance of the proposed receivers which are compared to some state-of-the-art supervised techniques